2007
DOI: 10.1097/cji.0b013e318031b53b
|View full text |Cite
|
Sign up to set email alerts
|

Targeting, Imaging, and Therapy Using a Humanized Antiprostate Stem Cell Antigen (PSCA) Antibody

Abstract: The murine 1G8 (micro1G8) monoclonal antibody directed against prostate stem cell antigen (PSCA) prevents prostate tumor establishment, growth, and metastasis in murine models. To further delineate in vivo targeting properties, micro1G8 was radiolabeled with In-111 and evaluated in nude mice bearing PC3-PSCA xenografts. Tumor activity ranged from 11.8% to 17.1% injected dose per gram (ID/g) at 24 to 96 hours postinjection. To extend the clinical applicability of micro1G8, a chimeric 1G8 antibody was produced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 42 publications
0
69
0
Order By: Relevance
“…Hundreds of prostate lineage-unique proteins (PLUP) exist among the 37,000ĂŸ normal human prostate lineage-unique open reading frames in EST and SAGE libraries (13 177 Lu-J591 combined with hormonal therapy are now being evaluated for OS benefit in patients with mCRPC. In addition to anti-PSMA, PSCA antibodies and minibodies both show impressive affinity, localization, and antitumor effects in chemotherapy and hormone-refractory xenograft models of human prostate cancer (15).…”
Section: Targeting Prostate Lineage-unique Antigens: Monoclonal Iggs mentioning
confidence: 99%
“…Hundreds of prostate lineage-unique proteins (PLUP) exist among the 37,000ĂŸ normal human prostate lineage-unique open reading frames in EST and SAGE libraries (13 177 Lu-J591 combined with hormonal therapy are now being evaluated for OS benefit in patients with mCRPC. In addition to anti-PSMA, PSCA antibodies and minibodies both show impressive affinity, localization, and antitumor effects in chemotherapy and hormone-refractory xenograft models of human prostate cancer (15).…”
Section: Targeting Prostate Lineage-unique Antigens: Monoclonal Iggs mentioning
confidence: 99%
“…To redirect T lymphocytes to PSCA and MUC1, we used a second-generation PSCA-specific CAR and MUC1-specific CAR, which respectively consisted of the single-chain variable fragments (scFvs) derived from the humanized 1G8 anti-PSCA antibody 33 and anti-MUC1 HMFG2 monoclonal antibody, 34 and signaling domains from the co-stimulatory molecule CD28 and the CD3z (Fig. 3A).…”
Section: Generation Of Car T Cells Targeting Psca and Muc1mentioning
confidence: 99%
“…To generate CAR-PSCA and CAR-MUC1 lentiviral vectors, scFvs derived from the humanized 1G8 anti-PSCA antibody 33 and anti-MUC1 HMFG2 monoclonal antibody 34 were codon optimized and synthesized by Genscript (Piscataway, NJ, USA). These scFvs were cloned into a CAR-encoding vector backbone comprising the CD8a leader sequence, human IgD hinge, portions of the CD28 transmembrane domains and the CD28 and CD3zendodomains within the second-generation lentiviral vector pWPXLd.…”
Section: Vector Designmentioning
confidence: 99%
“…PSCA is additionally overexpressed in bladder and pancreatic cancers. Although previous work has shown that 124 I-labeled anti-PSCA minibodies exhibit high-contrast images of PSCA-expressing targets at relatively early time points (6–44 h), no work has yet been done to quantify the kinetics of these systems (28,29). …”
mentioning
confidence: 99%